2020
DOI: 10.1155/2020/4812759
|View full text |Cite
|
Sign up to set email alerts
|

Etiologies and Treatment Burden in Adult Patients with Pure Red Cell Aplasia: A Single-Center Experience and Review of Literature

Abstract: Background. Pure red cell aplasia (PRCA) is less common blood disorder; the causes and the treatments of PRCA are varied. Methods. We conducted a retrospective study during January 2010–December 2017, to explore the etiologies and to evaluate the response and treatment burden in adult patients with PRCA. Results. Of 32 PRCA patients, median age was 57 years (18–90 years). Median hemoglobin level and reticulocyte count at the time of diagnosis were 5.6 g/dL (3.3–7.3 g/dL) and 0.3% (0.1–0.7%), respectively. Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…In this case, our suspicions were based on her underlying autoimmune disease and past exposure to 2 types of rHuEPO (continuous erythropoietin receptor activator [CERA] and biosimilar erythropoietin alpha). PRCA is rare in patients with SLE [ 16 , 17 ]. A retrospective study [ 17 ] we performed January 2010 to December 2017 in our center showed that nearly 50% of the etiology was ESA-related PRCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, our suspicions were based on her underlying autoimmune disease and past exposure to 2 types of rHuEPO (continuous erythropoietin receptor activator [CERA] and biosimilar erythropoietin alpha). PRCA is rare in patients with SLE [ 16 , 17 ]. A retrospective study [ 17 ] we performed January 2010 to December 2017 in our center showed that nearly 50% of the etiology was ESA-related PRCA.…”
Section: Discussionmentioning
confidence: 99%
“…PRCA is rare in patients with SLE [ 16 , 17 ]. A retrospective study [ 17 ] we performed January 2010 to December 2017 in our center showed that nearly 50% of the etiology was ESA-related PRCA. Only 3% were related to SLE, which responded poorly to immunosuppressive agents.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical outcome of PRCA is variable from complete remission to fatal, and it depends upon the cause and the types of treatment [ 5 , 17 , 22 24 ]. Some patients with PRCA show no response to treatment [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical outcome of PRCA is variable from complete remission to fatal, and it depends upon the cause and the types of treatment [11,18,23]. Some patients with PRCA show no response to treatment [11].…”
Section: Discussionmentioning
confidence: 99%
“…Naparuck et al has reported favourable treatment response in groups of parvovirus B19 infection, drug-(non-erythropoiesisstimulating agent (ESA)-) induced PRCA and idiopathic PRCA. The outcome has been unfavourable in groups of ESA and thymoma-induced PRCA, even they were receiving immunosuppressants or chemotherapy, respectively [23]. However, Hirokawa et al has reported cyclosporine producing excellent responses in patients with thymoma-associated PRCA, although limited information suggests that patients with thymoma-associated PRCA have poor prognoses [24].…”
Section: Discussionmentioning
confidence: 99%